Association of high blood pressure with renal insufficiency: role of albuminuria, from NHANES, 1999-2006. - Ping Yan (Public Library of Science (PLoS), 2012)
Background The relationship between hypertension and kidney disease is complicated. Clinical trials found intense blood pressure control was not associated with alterations in glomerular filtration rate (GFR) in all patients but did slow the rate of GFR decline among those with a higher baseline proteinuria. However, the underlying mechanism has been unclear. Methods We tested the hypothesis that the association between high blood pressure and renal function is modified by albuminuria status by conducting analyses in a cross-sectional study with 12,440 adult participants without known kidney diseases, diabetes or cardiovascular diseases, participating in the National Health and Nutrition Examination Survey (NHANES) 1999-2006. Results 1226 out of 12440 were found to have unknown high blood pressure and 4494 were found to have reduced renal function. Overall, a moderate association was found between high blood pressure and renal function insufficiency in all participants analyzed. However, among participants with albuminuria, the prevalence of moderate-severe renal insufficiency substantially and progressively increased from normal subjects to prehypertensive and undiagnosed hypertensive subjects (1.43%, 3.44%, 10.96%, respectively, P for trend<0.0001); on the other hand, the prevalence of undiagnosed hypertension was also significantly higher among subjects with moderate-severe renal insufficiency than those with mild renal insufficiency (35.54% Vs 19.09%, P value <0.05), supporting an association between hypertension and renal function damage. In contrast, no association between hypertension and renal insufficiency was observed among those without albuminuria in this population. Similar findings were observed when the CKD-EPI equation was used. Conclusions The association between high blood pressure and reduced renal function could be dependent upon the albuminuria status. This finding may provide a possible explanation for results observed in clinical trials of intensive blood pressure control. Further studies are warranted to confirm our findings.